Ethnomathematics Mencak at Traditional Wedding Ceremonies in Seluma Regency - Lorenza Puspita Sari; Nyayu Masyita Ariani; Kashardi Kashardi (Kognitif: Jurnal Riset HOTS Pendidikan Matematika, 2026)
Mathematics not only developed as an abstract science, but it was also present and rooted in the cultural practices of society. One form of this linkage can be studied through an ethnomathematical approach, which plays an important role in the preservation of local culture as well as the development of cultural-context-based mathematics learning. This research aims to identify and describe the ethnomathematical concepts contained in the mencak tradition as the cultural heritage of the community. This research uses a qualitative method with research subjects consisting of traditional leaders and practitioners of the mencak tradition who understand the process and meaning of the implementation of the tradition. Data was obtained through observation, in-depth interviews, and documentation, then analyzed using Miles and Huberman's interactive analysis model which included data reduction, data presentation, and conclusion drawn. The results of the study show that in the movements and formations in the mencak tradition there are mathematical concepts in the form of taper angles, right angles, blunt angles, straight angles, and reflex angles. These concepts arise from the position of the body, the direction of movement, and the patterns of interaction between traditional actors, which reflect mathematical understanding that is naturally integrated in cultural practice. These findings show that the mencak tradition has potential as a source of ethnomathematics-based mathematics learning.